Earth! my first 4.54 billion years - McAnulty, Stacy (Henry Holt and Company, 2017)
The Earth introduces readers to key moments in the planet's life, from its formation over four billion years ago to the present, including the Earth's position in the solar system, its layers, and when plants and animals began to inhabit the planet